Modified residual soil for the fine-grained layer of capillary barriers - I Gbe Budi Indrawan (2008)
[THIS THESIS CONSISTS OF TWO (2) PARTS – THIS IS PART 1]. Capillary barrier, which is commonly defined as an earthen cover system consisting of a fine-grained soil overlying coarse-grained soil, has potential to be used as a slope protection technique. The contrast in hydraulic properties of the fine-grained layer and coarse-grained layer under unsaturated conditions impedes the downward water movement into the underlying protected system as demonstrated in this study. The Bukit Timah residual soil has been considered to be a suitable material for the fine-grained layer of capillary barrier system. Although residual soils are abundant in Singapore, it has high fine contents that cause the residual soil to have a low permeability and high shrinkage characteristics upon drying. In order to improve the hydraulic properties and the volumetric shrinkage characteristics, the residual soil was mixed with coarse-grained contents (i.e., gravelly sand or medium sand) or lime at different percentages. Results of the laboratory tests showed that the saturated permeabilities of the residual soil-gravelly sand mixtures and the residual soil-medium sand mixtures increased with the increase in the coarse-grained contents, while the saturated permeabilities of the residual soil-lime mixtures decreased with the increase in the lime percentages. The air-entry values of the soil-water characteristic curves (SWCCs) of the residual soil-gravelly sand mixtures and the residual soil-medium sand mixtures decreased with the increase in the coarse-grained contents and increased with the increase in the lime percentages. The permeability functions of the soil mixtures became steeper with the increase in the percentages of coarse-grained content and lime.